The social construction of the competent, self-governed child in documentation: Panels in the Swedish preschool. (March 2017) - Liljestrand, Johan; Hammarberg, Annie
Documentation has become an important issue for policy, practice and accountability in many national contexts. The documentation of children's activities is a requirement in the national syllabus for the Swedish preschool. However, the documentation of children is always a social construction that focuses on certain things and excludes (possible) others. Such constructions can be linked to broader discourses of the competent and self-governed child, and the tendency to label the child as autonomous and competent in policy documents. The purpose of this article is to explore how constructions of the competent and self-governed child are performed in documentation panels in Swedish preschools. The theoretical framework is taken from visual methodology combined with an analysis of intertextuality. Three images (pictures and written text) of the preschool are discerned: the child as a good pal; the child as an autonomous investigator; and the child as a public speaker. In all three images, the children are depicted as competent in different respects. The result is discussed by relating the findings to broader discourses emphasising the competent and self-governed child.